1989
DOI: 10.1038/hdy.1989.105
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear DNA variation in diploid and polyploid taxa of Larrea (Zygophyllaceae)

Abstract: A study of nuclear DNA content was made in telophase nuclei (2C) of the root apex of germinating seed in nine populations of the following species and cytotypes of Larrea: L. nitida (2x), L. divaricata (2x), L. cuneifolia (4x) and L. tridentata (2x, 4x, 6x). There were no significant differences in DNA content per basic monoploid genome among the diploid taxa nor between the latter and the tetraploid, among tetraploids or between tetraploids and the hexaploid. On the other hand, the difference between means wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…No positive association can be made between the ploidy level and aridity as reported in other plants (e.g., STEBBINS 1985; POGGIO et al 1989;BARRETT and CASE 2006;ASHMAN 2007). However, polyploidy and gender dimorphism have evolved multiple times in concert within the genus (LEVIN et al 2007).…”
Section: Discussionmentioning
confidence: 92%
“…No positive association can be made between the ploidy level and aridity as reported in other plants (e.g., STEBBINS 1985; POGGIO et al 1989;BARRETT and CASE 2006;ASHMAN 2007). However, polyploidy and gender dimorphism have evolved multiple times in concert within the genus (LEVIN et al 2007).…”
Section: Discussionmentioning
confidence: 92%
“…Cav. the ploidy level increases towards the west with a concomitant increase in aridity (HuN-ZIKER et al 1977, 1978POGGIO et al 1989). The increase of ecological diversity and the opening of new habitats for colonization of xeric areas, as a result of climatic change, provides an opportunity for polyploids to exhibit their adaptive abilities and as a contribution to the fight against deserts growth in patagonia.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been demonstrated that important ecological characteristics of plant species in natural habitats vary with genome size, e.g. timing of spring growth, cell size and rate of leaf expansion in early season growth (Grime et al, 1985), frost resistance (Macgillivray and Grime, 1995), xeric conditions (Poggio et al, 1989) and altitude .…”
Section: Introductionmentioning
confidence: 99%